Upah Menurut Jenis Kelamin Di Indonesia Tahun 2013 - HAMID, Abdul ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A half of total population of Indonesia are women who commonly have high vulnerability in labor market. As a common knowledge, they earn less than men. In other side, Indonesia is one of country that committed to fight gender discrimination through several policies. But, what about the achievement in 2013?This research focuses on identifying earning differences based on sex. It also specifically identify earning gap between men and women based on individual criteria such as differences of educational, occupational, industrial, and provincial characteristics. The main data were based on national labour survey of Indonesia (Sakernas) February 2013 collected by Statistic of Indonesia (BPS). The data were analyzed through simple quantitative descriptive analysis, using cross tabulation and phi correlation. The outputs were represented by distribution diagrams and map. The results show that number of male workers in Indonesia in 2013 were generally higher than of female workers. Moreover male workers on average still earned more (Rp 1,578,000) than female workers who earned only Rp 1,257,000 that was under proper minimum wage. The results also show that low of female’s earning appears on both educational and occupational classifications. But, based on industrial and provincial classification, such women earned more than men such as in North Sulawesi and Gorontalo.